A comprehensive classification of MANETs routing protocols - Ahmed, Diaa Eldein Mustafa; Khalifa, Othman Omran (International Journal of Computer Applications Technology and Research, 2017)
Mobile Ad hoc Networks (MANETs) is self-organized and self-configured networks that doesn’t need any cellular infrastructure such as access point (AP), base station (BS) or fixed transmission links. Routing is point of research focus since the invention of commercialized mobile ad-hoc networks. In the literature the classical taxonomy of MANETs routing protocols based on the route computation process subdivided into: Proactive (Table -Driven), Reactive (On-Demand) and Hybrid (inherit both features of the proactive and reactive).However this classification hide other types of MANETs routing protocols play a significant roles nowadays such as(Multicast , Energy and Power- aware, Geographical routing and Hierarchical Routing). This paper provides a comprehensive study of MANETs basic taxonomy of routing protocols. In addition intense comparison between some examples of each routing protocols category has been made to further facilitate research in this area.